Folded meander line antenna for wireless M‐Bus in the VHF and UHF bands. Issue 15 (9th July 2015) - Loutridis, A.; John, M.; Ammann, M.J.
Abstract : The first dual‐band printed monopole antenna for wireless M‐Bus and M2M applications with operation in the VHF and lower UHF bands is presented. The antenna operates at 169 and 433 MHz. The miniaturisation of the proposed compact antenna is based on a double‐sided meandering structure offering an easily controlled large frequency ratio. The antenna provides high total efficiency and gain in both bands. Measured and simulated results are reported.